2017
DOI: 10.1016/j.celrep.2017.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Impaired Endocannabinoid-Dependent Long-Term Depression in the Lateral Habenula in an Animal Model of Depression

Abstract: Abnormal potentiation in the lateral habenula (LHb) has been suggested to mediate depression-like behaviors. However, the underlying mechanisms of the synaptic efficacy regulation of LHb synapses and the potential for their modulation are only poorly understood. Here, we report that long-term synaptic depression (LTD) occurs in the LHb upon both low-frequency stimulation (LFS) and moderate-frequency stimulation (MFS). LFS-induced LTD (LFS-LTD) is accompanied by a reduction in presynaptic release probability, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 40 publications
7
42
3
Order By: Relevance
“…Hu et al ( 2011 ) showed that rats exposed to chronic restraint stress presented an impaired endocannabinoid-mediated DSI in the CA 1 pyramidal neurons of the dorsal hippocampus. Similar alterations in endocannabinoid-mediated plasticity were reported in other brain regions, such as the amygdala, habenula, striatum and the BNST (Rossi et al, 2008 ; Patel et al, 2009 ; Glangetas et al, 2013 ; Di et al, 2016 ; Park et al, 2017 ).…”
Section: Stress Induces Changes In Cannabinoid-mediated Hippocampal Nsupporting
confidence: 62%
See 1 more Smart Citation
“…Hu et al ( 2011 ) showed that rats exposed to chronic restraint stress presented an impaired endocannabinoid-mediated DSI in the CA 1 pyramidal neurons of the dorsal hippocampus. Similar alterations in endocannabinoid-mediated plasticity were reported in other brain regions, such as the amygdala, habenula, striatum and the BNST (Rossi et al, 2008 ; Patel et al, 2009 ; Glangetas et al, 2013 ; Di et al, 2016 ; Park et al, 2017 ).…”
Section: Stress Induces Changes In Cannabinoid-mediated Hippocampal Nsupporting
confidence: 62%
“…Although stressful experiences are definite risk factors for the precipitation of psychiatric disorders, caution must be taken to translate the preclinical data directly into human pathology. Moreover, besides the hippocampus, other brain regions such as the prefrontal cortex, amygdala (Hill et al, 2010 ), nucleus accumbens (Bosch-Bouju et al, 2016 ), the paraventricular nucleus of the hypothalamus (Wamsteeker et al, 2010 ), lateral habenula (Park et al, 2017 ) and the periaqueductal gray matter (Moreira et al, 2009 ), are involved in stress-induced behavioral and neuroplastic consequences. These regions are modulated by eCBs and, therefore, are also potential therapeutic targets for cannabinoid drugs (For additional information about this topic, please read the excellent reviews by Gorzalka and Hill ( 2009 ), Riebe and Wotjak ( 2011 ), Hillard et al ( 2016 ), Lutz et al ( 2016 ) and Balsevich et al ( 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, down-regulation of βCaMKII levels, blocking its activity or its target molecule the glutamate receptor GluR1 in cLH rats reversed depressive symptoms (Li et al, 2013). In contrast with the persistent lifelong stress disposition of cLH rats, acute stress increased both isoforms, αCaMKII and βCaMKII (Park et al, 2017a). Furthermore, CaMKII is implicated in producing the aberrant endocannabinoid signaling profile that facilitates LHb hyperexcitability following stress (Park et al, 2017a; Authement et al, 2018).…”
Section: Molecular Mechanisms Underpinning Lhb Hyperactivity In Deprementioning
confidence: 92%
“…Furthermore, sex-dependent effects of CUS were analyzed in Sprague-Dawley rats, obtaining lower and higher CB1r protein expression in males and females, respectively, whereas increased FAAH levels were present in both sexes (192). In addition, further studies employing the CUS procedure specifically focused on CB1rmediated signaling, revealing significant loss of function disturbances in the NAc (193) and in the LHb (194). Moreover, apart from stress-related animal models, Flinders Sensitive Line (FSL) or Wistar Kyoto (WKY) rats are wellknown genetic rat models of depression that were recently used to exhaustively analyze disturbances in different components of the ECS in specific brain regions and plasma (195,196).…”
Section: Animal Studiesmentioning
confidence: 99%